(untitled) (Research, Society and Development, 2021)
Currently, it is known how important and necessary training in higher education is. However, the greatest concern of teachers is not only the quality of the content that is passed on, but also the development of a critical sense. The objective of the research is to report the use of the mock trial in different courses and to analyze this active methodology in the Veterinary Medicine course. The research was carried out in the year 2021. The data presented were collected in the literature available in CAPES electronic journals: Scopus, Google Scholar, Pubmed and Scielo, having as keywords ’’ mock trial ’’ and ’’ Veterinary ’’, as well as in books for theoretical formulation of the review. When analyzing the data referring to the research, it is seen that the use of the mock trial in veterinary medicine is scarce, however, its use in the disciplines is essential, since it is an area of health, needing to train professionals capable of having critical and reflective thinking, as well as knowing how to act under pressure.